Integration of Religion and Culture Study of Islamic Leadership West Java, Indonesia - Adon Nasurullah Jamaludin; Eri Novari (Khazanah Sosial, 2022)
This research departs from the relationship between religion and culture. Both are different but have a close relationship and complement each other (influence). Leadership is action and behavior (leadership as act and behavior). Meanwhile, there are two sources of human action and behavior, namely religion and culture. Religion and culture have their respective values for humans. Religious values come from God while cultural values come from humans as actors of creation with members of the community. Human actions and behavior arise from the meaning of religious and cultural values. The question is whether leaders in Sundanese society are influenced by religious (Islam) and cultural values (Sundanese culture). This research chooses a study of Nyunda, Islamic (Nyantri) and Nyunda-Islami Leadership in Sundanese Leaders in West Java. This research method uses descriptive-analytic with the aim of getting a comprehensive picture related to the research focus. The results of this research show that religion and culture complement and influence leadership in Sundanese society. Religion and culture underwent a process of acculturation and assimilation, resulting in a dialectic between religious values (Islam) and cultural values (local wisdom), which gave birth to the philosophy or way of life of the Sundanese. One of them is the Sundanese leadership philosophy, namely the integration of religious and cultural values, which gave birth to three leadership characters in Sundanese society, namely (1). The Sundanese Leadership that Nunda. (2). Islamic Sundanese leadership (nyantri). (3). The Sundanese leadership that has both are Nyunda-Islami.